A NEW CEPHALINE GREGARINE LIPOSCELISUS DYTISCUSI N. SP. FROM THE GUT OF A BEETLE, DYTISCUS SP. - KALAVATI, C.; RAO, D.D.V. PRASADA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1995)
A new cephaline gregarine Liposcelisus dytiscusin. sp. (Gregarinida: Didymophyidae) from the gut of a coleopteran insect Dytisus sp. is described.